Internet connectivity disruption in France (France) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in France. Data sourced from IODA.
Network Disruption Incident ID: FR-2026-0010. Severity: critical. Confidence: 67%